Immunohistochemical and immunocytochemical study of mechanoreceptors in anterior cruciate ligament reconstruction with the remnant-preserving technique using Achilles tendon allografts - Keun Churl Chun; Sung Hyun Lee; Jeong Woo Kim; Eun Jung Jin; Kwang Mee Kim; Churl Hong Chun (Journal of Orthopaedic Surgery and Research, 2017)
Abstract Background Attempts have been made to validate the significance of remnant preservation with anterior cruciate ligament (ACL) reconstruction using immunohistochemical and immunocytochemical techniques. The purpose of this study was to examine the expression of mechanoreceptors in the remnant tissue of ACL reconstruction performed with the remnant-preserving technique. Methods Tissue samples were obtained from 10 patients who underwent ACL reconstruction with the remnant-preserving technique. The specimens were obtained from remnant ACL tissue and Achilles allografts superficially and at the tibial attachment. The control group consisted of three normal ACLs procured from young males who underwent partial meniscectomy. Tissues and cells from the ACL remnants and Achilles allografts were characterized using hematoxylin and eosin (H&E) staining and immunohistochemical, immunocytochemical, and immunoblotting assays. In particular, the sensitivity of neural cell validation was improved using nerve growth factor (NGF) to stimulate the expression of neural cells. Results The results are summarized as follows. (1) In H&E staining and immunohistochemical assays, no neural cells were detected in remnant or allograft tissue. (2) In the immunocytochemical study, neural cells were detected in remnant tissue. (3) The increased proliferation of remnant ACL cells with NGF treatment suggested their identity as neural cells. (4) NGF treatment also stimulated protein and RNA expression of Nestin (a specific marker for neural cells) in remnant ACL cells. Conclusions The improved immunocytochemical methodology proved useful. Although mechanoreceptors were detected relatively less frequently than expected, the authors consider that this finding does not negate the necessity of remnant-preserving ACL reconstruction.